Interaction of ultrasound with microporous polyethylene scaffolds. (October 2019) - Zhao, Liuxian; Lam, Yee Cheong; Lai, Chang Quan
Abstract: Ultrasound – stimulated healing in porous scaffolds has generated much interest in recent years. Most of the studies attempting to uncover the mechanisms behind this process, however, have mainly focused on the biochemical aspects and neglected the mechanical interaction between the ultrasonic waves and porous scaffolds. Such interactions are important, as they determine the distribution of ultrasonic waves around and within the scaffolds, which affects the local physical environment that, in turn, stimulates the biological responses. Here, we aim to identify the physical mechanism behind this interaction and elucidate the factors involved. To achieve this, microporous scaffolds were first fabricated by sintering monodisperse polyethylene (PE) colloids of different sizes. The transmission and reflection coefficients of these scaffolds were experimentally determined in an immersion setup, over the clinically relevant range of 1 – 30 MHz and compared with trends obtained from an analytical model and finite element simulations. The experimental and simulation data were found to agree well with the analytical solutions of Mie scattering, and the absorption coefficient was observed to depend more strongly on particle size than the exact shape or arrangement of the individual particles. Nonlinear fluctuations of the absorption coefficient with frequency were also predicted by the analytical model and observed experimentally. Furthermore, finite element simulations showed that the ultrasonic waves have poor penetration depth and scattering takes place mainly at the surface of the microporous scaffolds. Our results indicate that lower frequencies, smaller scaffold characteristic lengths, thinner scaffolds and orientations that maximize surface exposure of scaffolds to ultrasonic waves will enhance the penetration of ultrasound into the structures and potentially improve the rate of ultrasound-stimulated healing processes.